Peradaban Tionghoa selayang pandang - Nio, Joe Lan, 1904-1973. (Jakarta, Kepustakaan Populer Gramedia, 2013)
Social life and customs of Chinese people in Indonesia.
In Indonesian.
Keywords: Chinese -- Indonesia -- Social life and customs